Indigenous socioterritorial suffering: Socioterritorial conflicts and indigenous mental health in Brazil (Research, Society and Development, 2026)
This article aims to analyze socioterritorial conflicts involving Indigenous peoples in Brazil and discuss their impacts on mental health, proposing the analytical category of Indigenous socioterritorial suffering, understood as the psychosocial expression of territorial instability produced by persistent socioterritorial conflicts. This is a theoretical-analytical study with a qualitative approach, based on a critical narrative review of the literature on territory, political ecology, socioterritorial conflicts, and Indigenous mental health, as well as on the analysis of national institutional reports. The results indicate that territorial conflicts constitute structural and ongoing processes of instability that reorganize the material, relational, and symbolic conditions of collective existence. Data from the Indigenous Missionary Council reveal the predominance of state omission as the main form of violation, preceding invasions and direct confrontations. An association is observed between persistent territorial instability and the worsening of emotional suffering, including anxiety, depression, harmful alcohol use, and community disintegration. It is concluded that Indigenous mental health problems cannot be understood in isolation and should be analyzed through the articulation between territory, power relations, and public policies. The category Indigenous socioterritorial suffering contributes to overcoming individualizing approaches and guides territorially grounded and intersectoral care strategies.